Cultural Narratives and Global Impact: Analysing the Sociocultural Factors of One Piece (1999) in Japanese Manga - Aerlister Kessy La’eng; Rosli, Hafizah (Research in Management of Technology and Business, 2024)
This study aims to explore the significant sociocultural factors represented in Japanese Manga, with a focus on One Piece (1999), within the context of Japanese culture. The research seeks to establish the implications of these factors on the Manga’s reception and cultural transmission on a global scale. Through content analysis of nine scholarly literature reviews, key sociocultural factors within various fields were identified. These factors were then applied to analyse the case study of One Piece (1999), particularly its portrayal of Japanese culture and its contribution to global cultural dissemination. A total of 14 key elements were highlighted from the reviewed literature. The case study revealed three prominent elements cultural, societal, and linguistic that contribute to the immersive experience and compelling storyline of the Manga. The intricate relationship between culture, language, and society in One Piece (1999), serves as a powerful tool for connecting Japan with a global audience, making the Manga a significant cultural artifact that reflects and communicates Japan’s rich cultural heritage to the world.